Why The Rate Of Financing In Islamic Banks Is High? An Analysis Based On Malaysian Case - Irfan Syauqi Beik; Laily Dwi Arsyianti (Institute for Research and Community Empowerment (LPPM TAZKIA), 2008)
Islamic banking has grown rapidly and has become fi nancial-nerve centre in today’s world economy, particularly in the last three decades. It has attracted various entrepreneurs and enterprises to get its fi nancing. However, Islamic banks tend to have a higher rate of fi nancing compared to the conventional ones. This less competitiveness encourage the demand for Islamic products may fall leaving the Islamic banks. Good debtors opted for conventional loans since the interest rates paid were relatively lower and the rest (the bad debtors) successfully made their way to Islamic banks. Therefore, the nonperforming financing of Islamic banks is high. This paper attempts to analyze factors that determine high rate of fi nancing in Islamic banks, by taking the case of Malaysian Islamic banks. In this paper, the top three of Islamic banks and conventional banks are selected for comparison. It finds that high default premium and overheads per capital contribute signifi cantly to the high fi nancing rate. Hence, the Islamic banks should diversify their assets and implement universal banking concept.Keywords: Islamic bank, rate of fi nancing, NPF (Non-Performing Financing), universal banking system